Perovskite-Based Nanocomposite Electrocatalysts: An Alternative to Platinum ORR Catalyst in Microbial Fuel Cell Cathodes - Gopa Nandikes; Shaik Gouse Peera; Lakhveer Singh (Energies, 2021)
Microbial fuel cells (MFCs) are biochemical systems having the benefit of producing green energy through the microbial degradation of organic contaminants in wastewater. The efficiency of MFCs largely depends on the cathode oxygen reduction reaction (ORR). A preferable ORR catalyst must have good oxygen reduction kinetics, high conductivity and durability, together with cost-effectiveness. Platinum-based electrodes are considered a state-of-the-art ORR catalyst. However, the scarcity and higher cost of Pt are the main challenges for the commercialization of MFCs; therefore, in search of alternative, cost-effective catalysts, those such as doped carbons and transition-metal-based electrocatalysts have been researched for more than a decade. Recently, perovskite-oxide-based nanocomposites have emerged as a potential ORR catalyst due to their versatile elemental composition, molecular mechanism and the scope of nanoengineering for further developments. In this article, we discuss various studies conducted and opportunities associated with perovskite-based catalysts for ORR in MFCs. Special focus is given to a basic understanding of the ORR reaction mechanism through oxygen vacancy, modification of its microstructure by introducing alkaline earth metals, electron transfer pathways and the synergistic effect of perovskite and carbon. At the end, we also propose various challenges and prospects to further improve the ORR activity of perovskite-based catalysts.